Cultivating Equality: Advancing Gender Research in Agriculture and Food Systems, 12-15 October 2021 - Concept note - CGIAR GENDER Platform; Wageningen University & Research Centre (CGIAR GENDER Impact Platform, 2020)
To enhance the quality and influence of gender+ research in relation to food systems, agriculture and rural development by fostering the exchange of knowledge, strengthening capacities, and solidifying partnerships among CGIAR, universities, research institutes, and other gender research partners.